Performance of Xpert MTB/RIF by Using Gastric Lavage Sample in The Diagnosis of Pulmonary Tuberculosis in HIV Patients with Suspected Pulmonary Tuberculosis - Manuel Lamberto Willem Mboeik; Ceva Wicaksono Pitoyo; Teguh Harjono Karjadi; Anis Karuniawati; Esthika Dewiasty (Jurnal Penyakit Dalam Indonesia)
Introduction. Xpert MTB/RIF test on gastric lavage sample may improve pulmonary tuberculosis (TB) case finding, but its performance as a diagnostic test for pulmonary TB in HIV-infected adults patients has not been studied widely, including in Indonesia. This study aims to determine the performance of the Xpert MTB/RIF test in diagnosing pulmonary tuberculosis among HIV-infected adult patients with suspected pulmonary tuberculosis by using gastric lavage sample.